Pengaruh Kepemimpinan Kepala Sekolah terhadap Kinerja Guru Bimbingan dan Konseling melalui Motivasi Kerja - Yuliastini, Ni Komang Sri (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2021)
The purpose of this study was to determine the influence of the principal's leadership on the performance of guidance and counseling teachers through work motivation in Denpasar Private Vocational School. The research sample was 30 teachers of guidance and counseling of Denpasar Private Vocational School. The variables studied were the principal's leadership, work motivation, and the performance of the guidance and counseling teachers. The impact test will be carried out using path analysis techniques. From the research results it is known that there is a positive and significant relationship between all variables with the path coefficient as follows, (1) principal leadership on the performance of guidance and counseling teachers = 30.9% (2) principal leadership through work motivation on performance = 52 , 9%, (7) BK teacher competence through work motivation on performance = 30.4%. Based on these findings, the guidance and counseling teacher performance coaching is based on the leadership of the principal who is more concerned with mutual interests, in decision making involving guidance and counseling teachers, two-way communication, and always holding discussions and deliberations in deciding anything for the betterment of the school. In addition, the principal's support is sought in granting further study permits, training and workshops as well as giving awards to outstanding guidance and counseling teachers.